Pericyte-expressed Tie2 controls angiogenesis and vessel maturation - Teichert, Martin; Savant, Soniya; Augustin, Hellmut (Nature Communications, 2017)
The angiopoietins regulate vascular maturation, angiogenesis and lymphangiogenesis via their Tie receptors that were long believed to be endothelium-specific. Here the authors show that angiopoietins activate and control pericyte function through pericyte-expressed Tie2.
Gesehen am 14.09.2017